2019
DOI: 10.1002/asi.24259
|View full text |Cite
|
Sign up to set email alerts
|

Music discovery and revisiting behaviors of individuals with different preference characteristics: An experience sampling approach

Abstract: A mobile device‐enabled experience sampling study was conducted in which 44 participants answered questions about their music experiences 5 times a day for 2 weeks. Data regarding 4 aspects of their music‐related psychological traits—“music involvement,” “musical identity,” “preference diversity,” and “preference openness”—were also collected through a background questionnaire. A classification of music access modes was proposed based on the circumstances that lead to a music listening experience. A mixed regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…We also found that openness to novelty had a much higher correlation with involvement in movies than preference diversity did. Similarly, a strong correlation between openness to novelty and involvement was reported for music preference (Tang & Jhang, 2020).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…We also found that openness to novelty had a much higher correlation with involvement in movies than preference diversity did. Similarly, a strong correlation between openness to novelty and involvement was reported for music preference (Tang & Jhang, 2020).…”
Section: Discussionmentioning
confidence: 57%
“…The activity of "browsing friends' bookshelves"; a relatively imprecise yet diverse book discovery strategy, was most effective for individuals with high reading diversity. Preference diversity was also introduced in a music experience sampling study that explored the relationship between users' psychological traits and their music revisiting and discovery behaviors (Tang & Jhang, 2020). The findings indicated that individuals with high preference diversity in music derived more enjoyment from new music introduced by others than from listening to music already familiar to them.…”
Section: Preference Diversitymentioning
confidence: 99%
“…However, user data also contains special interests, and traditional algorithms set them as isolated points. The constructed model will exclude these points, causing significant errors in the prediction results [3]. In recent years, the K-means algorithm has attracted the attention of many scholars due to its simple and efficient clustering research.…”
Section: Introductionmentioning
confidence: 99%